2006
DOI: 10.1111/j.1365-2850.2006.00913.x
|View full text |Cite
|
Sign up to set email alerts
|

Further thoughts on the process of restraint

Abstract: The physical restraint of a disturbed person is a subject constant of psychiatry and is a challenge that particularly faces nurses working in acute inpatient settings. While other approaches to psychiatric treatment have been discarded (e.g. punishment, blood letting, trepanation, deep insulin therapy and so on) or evolved into new treatments (the use of medication), the act of physical restraint has remained largely unmodified. Given the ubiquity of physical restraint in psychiatry, particularly as a nursing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 7 publications
0
18
0
5
Order By: Relevance
“…The issues of staffing, skill mix, and the nature of the practice environment all need to be addressed to support nurses in their practice. Winship (2006) has suggested that mental health nurses need to aspire towards conceptualizing and delivering restraint with the maximum humanity possible and good insight into understanding the dynamics of the process.…”
Section: Resultsmentioning
confidence: 99%
“…The issues of staffing, skill mix, and the nature of the practice environment all need to be addressed to support nurses in their practice. Winship (2006) has suggested that mental health nurses need to aspire towards conceptualizing and delivering restraint with the maximum humanity possible and good insight into understanding the dynamics of the process.…”
Section: Resultsmentioning
confidence: 99%
“…Gözlem en az kısıtlayıcı ortamda ve düzeyde, kısa süreli olmalı-dır. [17,19,20] Ray ve arkadaşları çalışmalarında psikiyatrik tedavi ortamlarına kabul edilen hastaların %3 ile %20'sine aralıklı, göz ve kol mesafesinde gözlem uygulandığını belirtmişlerdir. [14] Akut Bakım Psikiyatri Kliniğinde Gözlemci Olma Risk altındaki hastanın gözlemlenmesi yüksek düzeyde beceri gerektiren bir aktivitedir.…”
Section: Akut Psikiyatri Kliniğinde Gözlem Düzeyleriunclassified
“…Akut bakımda hasta göz-lemlenmesi ile ilgili yaşanan en önemli etik problemler; gözlem hakkında hasta ve ailesine bilgi verilmemesi, hastanın gizliliğine ve mahremiyetine özen gösterilmemesi, hastanın bireyselliğine/otonomisine müdahale edici olunmasıdır. [13,17,20 ] …”
Section: Akut Psikiyatrik Bakımda Gözlemin Etik Boyutuunclassified
See 1 more Smart Citation
“…They became very widely used (Gournay et al 1998) and, though broadly similar, there are still differences in implementation between services. Winship (2006) provides a fascinating history of the development of the use of mechanical and physical restraint from the 15 th century to the present day.…”
Section: Variation In Methods and Terminologymentioning
confidence: 99%